ANALISIS KESALAHAN SISWA PADA MATERI KUBUS & BALOK - Rokan, Najwah; Putri, Jihan Hidayah (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2023)
Researchers conducted research that aims to find out the problems faced by students when learning mathematics, which are the factors that cause errors in solving math problems. This error factor must be known so that it is easier to get solutions and parts that need to be emphasized during learning. This research is a qualitative descriptive study to analyze and describe the types of mistakes students make when working on cube and block math questions. The subjects of this study were 30 students of SMP Al Washliyah 8 Medan in class VIII-A. The written test is a data collection technique. The results of the student error analysis obtained: 1) 66.67% conceptual errors with a "high" error standard; 2) 33.34 % of procedural errors with a "very low" error standard; This leads to the conclusion that students' understanding of the cube and block material is low, and the teacher must pay attention to knowledge, emphasizing the important parts that students use. Based on the results of interviews with teachers in the field of study that "student mathematics here is in the low class, because almost 75% of students here do not like mathematics, they think mathematics is a difficult lesson to understand" I asked: "What causes students here to dislike mathematics thuk?” the teacher answered: "The reason students don't like math is when I explain math with formulas, at first they understand, but after I give questions or exercises with the formula but it's just a different location, students are immediately confused about doing it, students here understand formulas but can't apply them. the formula".